PENGARUH TIME BUDGET PRESSURE TERHADAP DYSFUNCTIONAL AUDIT BEHAVIOR DENGAN DIMODERASI LOCUS OF CONTROL: Studi Empiris pada Kantor Akuntan Publik di DKI Jakarta - Apriyani, Dewi; Setiawan, Temy (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This study aims to examine the effect of time budget pressure and locus of control on the dysfunctional audit behavior and to see whether the locus of control can moderate the relationship between time budget pressure and the dysfunctional audit behavior. Questionnaires are distributed to 201 auditor who act as respondents, but only 146 questionnaire thatcan be processed from 51 KAP in Jakarta. Data analysis is conducted using SmartPLS 3.0 program.The results showed that, partially, time budget pressure variable and external locus of control give significant influence to dysfunctional audit behavior while internal locus of control does not affect dysfunctional audit behavior. The external and internal variables of the locus of control are not able to moderate the time budget pressure relationship to the dysfunctional audit behavior. Another finding in the form of sensitivity analysis suggests that male respondents consider that time budget pressure and external locus of control are factors that encourage them to perform dysfunctional audit behavior while time budget pressure does not encourage female respondents to perform dysfunctional audit behaviors.